2018
DOI: 10.1002/ece3.3856
|View full text |Cite
|
Sign up to set email alerts
|

Postreproductive lifespans are rare in mammals

Abstract: A species has a post‐reproductive stage if, like humans, a female entering the adult population can expect to live a substantial proportion of their life after their last reproductive event. However, it is conceptually and statistically challenging to distinguish these true post‐reproductive stages from the usual processes of senescence, which can result in females occasionally surviving past their last reproductive event. Hence, despite considerable interest, the taxonomic prevalence of post‐reproductive stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
104
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 102 publications
5
104
0
Order By: Relevance
“…[1][2][3][4][5][6].2y intervals reported elsewhere[6,35]. As might be expected, our IBI estimate falls between those calculated for mothers whose offspring died before vs. after age four (2.2y and 5.7y, respectively;[6]), with our lower estimate reflecting the averaged effects of infant mortality on birth spacing.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…[1][2][3][4][5][6].2y intervals reported elsewhere[6,35]. As might be expected, our IBI estimate falls between those calculated for mothers whose offspring died before vs. after age four (2.2y and 5.7y, respectively;[6]), with our lower estimate reflecting the averaged effects of infant mortality on birth spacing.…”
supporting
confidence: 64%
“…Humans and chimpanzees, whose recent common ancestor dates to 4-8 million years ago [1,2], share behavioral adaptations and life history traits that distinguish them among other primates [3,4]. Except for menopause, which appears unique among mammals apart from a few toothed whale species [5], human fertility is similar to chimpanzees [6], and mortality profiles of modern hunter-gatherers are closer to chimpanzees than they are to today's lowest-mortality industrialized populations [7]. Nevertheless, there is great variation among human and chimpanzee life histories [8].…”
Section: Introductionmentioning
confidence: 99%
“…77 However, the extension of life well beyond the end of the reproductive lifespan is extremely rare and is limited only to humans and two species of whales. 55,74,[78][79][80] Based on genetic variation, it is well documented that comparison of long-lived cohorts and controls showed variation. Analysis of candidate genes such as insulin-like growth factor 1 (IGF-1) and forkhead box O-3 (FOXO3) have revealed that polymorphisms in these genes are associated with extreme longevity.…”
Section: F I G U R E 3 Correlation Of Cd33rsiglec Genes With Maximummentioning
confidence: 99%
“…Although the exact benefits of the presence of conspecifics vary with ecological conditions [15,16] (e.g. food abundance [17]), the presence of conspecifics is generally thought to increase the mean (or reduce the variance in) individual foraging performance [14,18]. Due to the challenges of setting up, and subsequently replicating, different social compositions in the field, few studies have been able to experimentally manipulate the social environment in vertebrate species and study its effects on foraging performance in the wild [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Sex is likely to be one of the prime individual-level traits influencing the potential benefit(s) of social foraging. Many individual-level characteristics that are predicted to modulate the effectiveness of social foraging mechanisms, such as social position [29], risk-sensitivity [30], energy requirement [31] and dominance [32], covary with sex [17,30,[33][34][35][36][37][38]. We may thus expect conspecific presence to have a stronger impact on foraging performance in one sex than the other [39,40].…”
Section: Introductionmentioning
confidence: 99%